The effectiveness of a structured education pulmonary rehabilitation programme for improving the health status of people with moderate and severe chronic obstructive pulmonary disease in primary care: the PRINCE cluster randomised trial. Issue 10 (4th June 2013) - Casey, Dympna; Murphy, Kathy; Devane, Declan; Cooney, Adeline; McCarthy, Bernard; Mee, Lorraine; Newell, John; O'Shea, Eamon; Scarrott, Carl; Gillespie, Paddy; Kirwan, Collette; Murphy, Andrew W
Abstract : Objective: To evaluate the effectiveness of a structured education pulmonary rehabilitation programme on the health status of people with chronic obstructive pulmonary disease (COPD). Design: Two-arm, cluster randomised controlled trial. Setting: 32 general practices in the Republic of Ireland. Participants: 350 participants with a diagnosis of moderate or severe COPD. Intervention: Experimental group received a structured education pulmonary rehabilitation programme, delivered by the practice nurse and physiotherapist. Control group received usual care. Main outcome measure: Health status as measured by the Chronic Respiratory Questionnaire (CRQ) at baseline and at 12–14 weeks postcompletion of the programme. Results: Participants allocated to the intervention group had statistically significant higher mean change total CRQ scores (adjusted mean difference (MD) 1.11, 95% CI 0.35 to 1.87). However, the CI does not exclude a smaller difference than the one that was prespecified as clinically important. Participants allocated to the intervention group also had statistically significant higher mean CRQ Dyspnoea scores after intervention (adjusted MD 0.49, 95% CI 0.20 to 0.78) and CRQ Physical scores (adjusted MD 0.37, 95% CI 0.14 to 0.60). However, CIs for both the CRQ Dyspnoea and CRQ Physical subscales do not exclude smaller differences as prespecified as clinically important. No other statistically significant differences between groups were seen. Conclusions: A primary care based structured education pulmonary rehabilitation programme is feasible and may increase local accessibility to people with moderate and severe COPD. Trial registration: ISRCTN52403063.